Community leadersâ perspectives on facilitators and inhibitors of health promotion among the youth in rural South Africa - Lydia Aziato; Wilson Majee; Karien Jooste; Michelle Teti (Elsevier, 2017)
Introduction: There are a number of factors that influence health promotion activities among the youth. This study sought to gain a comprehensive understanding of the facilitators and inhibitors of health promotion among the youth from the perspectives of community leaders in a rural setting in South Africa. Methods: The study adopted an exploratory, descriptive and contextual qualitative approach involving community leaders in rural South Africa. Data saturation occurred after individual interviews with 21 participants. Data analysis employed the principles of content analysis. Results: We found that facilitators of health promotion were access to education on the benefits of health promotion activities, efforts of organizations and community leaders/teachers, access to health care services and engaging in physical activities, and youth motivation and positive role modelling. The themes that described the inhibitors of health promotion were inadequate recreational and health facilities and health personnel, the impact of stringent religious doctrines, unemployment, social vices and poor parenting. Conclusion: We concluded that there is the need to implement more engaging activities and opportunities for the youth and parents in rural communities to enhance health promotion. Keywords: Health promotion, Young adults, Qualitative research, Rural community